Faktor-Faktor Yang Mempengaruhi Keputusan Konsumen Menggunakan jasa pada LPK Barokah Kota Bengkulu - Memet Pradana; Ida Anggriani; Abdul Rahman (UNIVED Press, 2023)
The purpose of this study is to determine the factors that influence consumer decision to use services at LPK Barokah Bengkulu City. The analytical method used were multiple linear regression, coefficient of determination (R2) and hypothesis testing (t test and F test) with the help of SPSS version 22 program. The sample in this study amounted to 52 respondents. Multiple linear regression results obtained Y = 0.426 + 0.181X1 + 0.306X2 + 0.294X3 + 0.198X4 + e. The constant value of 0.426 means that if cultural factor (X1), social factor (X2), personal factor (X3), psychological factor (X4), are considered equal to zero then the consumer decision to use services (Y) at LPK Barokah Bengkulu City is 0.426. From the results of the coefficient of determination obtained an R value of 0.997 and R Square (R2) obtained a value of 0.994 or (99.4%), meaning that the contribution/contribution of cultural factor (X1), social factor (X2), personal factor (X3), psychological factor (X4) on consumer decision to use services (Y) at LPK Barokah Bengkulu City collectively amounted to 99.4%, the remaining 0.6% was a contribution / contribution from other variables not examined in this study. The results of the t-test on cultural factor (X1) obtained a significance value of <0.05, which is 0.001 meaning that cultural factor have a significant effect on consumer decision to use services at LPK Barokah Bengkulu City. The results of the t-test on social factor (X2) obtained a significance value of < 0.05, which is 0.000, meaning that social factor have a significant effect on consumer decision to use services at LPK Barokah Bengkulu City. The results of the t-test on personal factor (X3) obtained a significance value of < 0.05, which is 0.000, meaning that personal factor have a significant effect on consumer decision to use services at LPK Barokah Bengkulu City. The results of the t-test on psychological factor (X4) obtained a significance value of <0.05, which is 0.001 meaning that psychological factor have a significant effect on consumer decision to use services (Y) at LPK Barokah Bengkulu City. Based on the F test, the significance value <0.05 is 0.000, meaning that simultaneously cultural factor, social factor, personal factor, psychological factor have a significant effect on consumer decision to use services at LPK Barokah Kota Bengkulu.